Game changers : the story of Venus and Serena Williams - Cline-Ransome, Lesa (Simon & Schuster Books for Young Readers, 2018)
Shares the story of the sisters and tennis stars, including their special relationship as sisters and best friends, their constant training as children, and their incredible success in professional tennis.